The Six Mile Water Revival of 1625: Ulster Presbyterianism as Background for the Last Will and Testament - Hower, Tyler (Stone-Campbell journal, 2004)
In the summer of 1625, a religious revival began in the town ofAntrim in the area of Northern Ireland known as Ulster. The SixMile Water Revival centered on an Arminian idea of communionthat transcended hierarchical church structure. The Cane RidgeRevival of 1801 Kentucky includes important similarities with theSix Mile Water Revival of 1625 Ulster. Both revivals combinedselect Arminian teachings with Presbyterianism to create a uniquefrontier faith.